Cell-Free DNA Promotes Thrombin Autolysis and Generation of Thrombin-Derived C-Terminal Fragments - Saravanan, Rathi; Choong, Yeu Khai; Lim, Chun Hwee; Lim, Li Ming; Petrlova, Jitka; Schmidtchen, Artur (Frontiers in Immunology, 2021)
Cell-free DNA (CFDNA) is the major structural component of neutrophil extracellular traps (NETs), an innate immune response to infection. Antimicrobial proteins and peptides bound to CFDNA play a critical role in the bactericidal property of NETs. Recent studies have shown that NETs have procoagulant activity, wherein CFDNA triggers thrombin generation through activation of the intrinsic pathway of coagulation. We have recently shown that thrombin binds to NETs in vitro and consequently can alter the proteome of NETs. However, the effect of NETs on thrombin is still unknown. In this study, we report that DNA binding leads to thrombin autolysis and generation of multiple thrombin-derived C-terminal peptides (TCPs) in vitro. Employing, a 25-residue prototypic TCP, GKY25, we show that TCPs bind NETs, thus conferring mutual protection against nuclease and protease degradation. Together, our results demonstrate the complex interplay between coagulation, NET formation, and thrombin cleavage and identify a previously undisclosed mechanism for formation of TCPs.